2013
DOI: 10.1530/eje-13-0441
|View full text |Cite
|
Sign up to set email alerts
|

Clinical phenotypes of Chinese primary hyperparathyroidism patients are associated with the calcium-sensing receptor gene R990G polymorphism

Abstract: Objective: The purpose of this study was to investigate the distribution of the A986S and R990G polymorphisms of the calcium-sensing receptor (CASR) gene in the Chinese population and whether there is an association between genetic variants and the risk of developing primary hyperparathyroidism (PHPT) and its associated clinical phenotypes. Methods: A total of 164 Chinese Han PHPT patients (M/F: 51/113) and 230 healthy controls (M/F: 50/180) were enrolled. The common clinical parameters of PHPT patients includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
(47 reference statements)
0
9
0
1
Order By: Relevance
“…For the associations between CaSR polymorphisms and urinary calcium concentration, ten papers [ 5 , 13 15 , 18 23 ] were retrieved according to the inclusion criteria. The process of study selection is also shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…For the associations between CaSR polymorphisms and urinary calcium concentration, ten papers [ 5 , 13 15 , 18 23 ] were retrieved according to the inclusion criteria. The process of study selection is also shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…However, a dozen cases of parathyroid adenomas associated with CASR mutations have been reported, with two families having adenoma and/or familial hyperplasia of the parathyroids with papillary microcarcinoma [7–14]. Moreover, the R990G variant of CaSR seems to be more common in the general Chinese population, but also in Chinese patients with hyperparathyroidism [15]. The coexistence of hyperparathyroidism and hypocalciuric hypercalcaemia syndrome was also identified in 4 out of 139 patients from a hyperparathyroid Caucasian population [16].…”
Section: Genetic Causesmentioning
confidence: 99%
“…Of those, four papers [26][27][28][29] showed that R990G gene polymorphism was associated with the risk of urolithiasis with variable odd ratio, ranging from 1.24 to 8.07 (G vs. R). On the other hand, four other studies [30][31][32][33] failed to confirm the correlation. Our pooled calculation revealed that R allele and RR genotype were associated with decreased risk of urolithiasis.…”
Section: Discussionmentioning
confidence: 82%